1995
DOI: 10.1144/gsjgs.152.2.0339
|View full text |Cite
|
Sign up to set email alerts
|

The geometry and evolution of a transpressional strike-slip system: the Carboneras fault, SE Spain

Abstract: The Carboneras fault system is a 40 km long, 1 km wide Neogene NE-SW-trending left-lateral transpressional strike-slip fault system which is part of the Trans-Alboran shear zone in SE Spain. The Carboneras fault system is an anastomosing array of sub-vertical, individual fault planes or fault zones which surround pods or lenses of less intensely strained rocks. Displacements along the individual fault planes exhibit reverse components of slips and form positive flower structures. Faults have either sharp bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 20 publications
(5 reference statements)
0
49
0
Order By: Relevance
“…We have included the onshore segment due to its proximity to the coast, therefore dividing the Carboneras Fault into three segments: the onshore segment, here called "Carboneras Fault Northern" (CFN); the northern offshore segment; "Carboneras Fault Central" (CFC) and the southern offshore segment, "Carboneras Fault Southern" (CFS). The characteristics of the onshore segment are very similar to those of the northern offshore segment (Keller et al, 1995;Grana et al, 2006;Moreno et aI., 2008).…”
Section: Carboneras Faultmentioning
confidence: 71%
“…We have included the onshore segment due to its proximity to the coast, therefore dividing the Carboneras Fault into three segments: the onshore segment, here called "Carboneras Fault Northern" (CFN); the northern offshore segment; "Carboneras Fault Central" (CFC) and the southern offshore segment, "Carboneras Fault Southern" (CFS). The characteristics of the onshore segment are very similar to those of the northern offshore segment (Keller et al, 1995;Grana et al, 2006;Moreno et aI., 2008).…”
Section: Carboneras Faultmentioning
confidence: 71%
“…Marín-Lechado et al, 2005). These events have been mainly attributed to the motion along the Carboneras fault system (Keller et al, 1995). On the other hand, it has been suggested that the 1910 Adra Earthquake (M w = 6.1, I 0 = VIII MSK in Adra) was probably generated by N120-N130 trending faults offshore (Stich et al, 2003b), although, the tectonic source of this earthquake is still unknown.…”
Section: Tectonics and Seismicity Of The Adra-almería Marginmentioning
confidence: 99%
“…4A; Galindo-Zaldívar, 1986). fault segment runs from Los Guardianes, near Polopos village, to the southern boundary of Sierra Cabrera antiform with an ENE-WSW trend, being called the Polopos fault (Keller et al, 1995) or the South Gafarillos fault ( Fig. 4; Giaconia et al, 2012).…”
Section: Miocene Tectonic Structuresmentioning
confidence: 99%
“…3C and 4C). Southdipping reverse faults form the north boundary of the Sierra Cabrera (Booth-Rea et al, 2004), locally affecting Quaternary sediments (Sanz de Galdeano, 1987), and north-dipping reverse faults constitute the southern edge of the Sierra (Keller et al, 1995).The CuaTeNeo (Cuanti¿FLDFLyQ GH OD 7HFWyQLFD DFWXDO \ 1HRWHFWyQLFD *36 QRQ permanent network was installed in 1996 to quantify the deformation in the Eastern Betic Cordillera. The network consists of 15 monuments covering an area of 120x50 km in Murcia and Almería (Colomina et al, 1998;Khazaradze et al, 2007 and2008).…”
Section: Active Tectonic Structuresmentioning
confidence: 99%